Pralsetinib in RET fusion-positive non-small-cell lung cancer: A real-world data (RWD) analysis from the Italian expanded access program (EAP). (December 2022) - Passaro, Antonio; Russo, Giuseppe Lo; Passiglia, Francesco; D'Arcangelo, Manolo; Sbrana, Andrea; Russano, Marco; Bonanno, Laura; Giusti, Raffaele; Metro, Giulio; Bertolini, Federica; Grisanti, Salvatore; Carta, Annamaria; et al.
Highlights: Data from the largest real-world experience with pralsetinib in NSCLC are presented. Pralsetinib was administered to 62 patients at 20 Italian centres. Pralsetinib showed objective response rate (ORR) of 66%, intracranial ORR was 83%. Toxicity profile was consistent with previous reports. Abstract: Objectives: The selective RET-inhibitor pralsetinib has shown therapeutic activity in early clinical trials in patients with non-small cell lung cancer (NSCLC) harboring rearranged during transfection ( RET ) gene fusions. To date, the real-world efficacy of pralsetinib in this population is unknown. Materials and methods: A retrospective efficacy and safety analysis was performed on data from patients with RET -fusion positive NSCLC enrolled in the pralsetinib Italian expanded access program between July 2019 and October 2021. Results: Overall, 62 patients with RET -fusion positive NSCLC received pralsetinib at 20 Italian centers. Next-generation sequencing was used to detect RET alterations in 44 patients (73 %). The most frequent gene fusion partner was KIF5B (75 % of 45 evaluable). Median age was 62 years (range, 36–90), most patients were female (57 %) and never smokers (53 %). Brain metastases were known in 18 patients (29.5 %) at the time of pralsetinib treatment. 13 patients were treatment naïve (unfit for chemotherapy), 48 were pretreated (median number of previous lines: 1, range, 1–4). The objective response rate (ORR) was 66 % [95 % confidence interval (CI), 53–81] in the evaluable population (n = 59). The disease control rate (DCR) was 79 %. After a median follow-up of 10.1 months, the median progression free survival was 8.9 months (95 %CI, 4.7–NA). In patients with measurable brain metastases (n = 6) intracranial ORR was 83 %, intracranial DCR was 100 %. Overall, 83.6 % of patients experienced any-grade treatment-related adverse events (TRAEs), 39 % grade 3 or greater (G ≥ 3). The most common G ≥ 3 TRAEs were neutropenia (9.8 %), dry mouth/oral mucositis (8.2 %), and thrombocytopenia (6.6 %). Seven patients (12 %) discontinued pralsetinib due to TRAEs, twenty-six had at least one dose level modification due to TRAEs. Two treatment-related deaths were observed (1 sepsis, 1 typhlitis). Conclusions: In the real-world setting, pralsetinib confirmed durable systemic activity and intracranial response in RET- fusion positive NSCLC. Toxicity profile was consistent with previous reports.